Analisis Yuridis Terhadap Penegakan Hukum dalam Kasus Pemerkosaan Anak dibawah Umur - Prihatiningtyas, Adelia Putri (UM Purwokerto Press, 2024)
Rape is an act committed by a man to force a woman to have sexual intercourse outside of marriage. Rape is one of the most traumatic things for women, especially children who are victims of rape. Rape of minors is a very serious and detrimental form of crime, which has lasting psychological, physical and social impacts on the victim and society in general. In many countries, the rape of minors is often an undeniable problem in the realm of law and humanity. In the Indonesian context, cases of rape of minors are also an urgent issue that must be handled firmly by the legal system. However, law enforcement in cases like this often faces various obstacles, ranging from a lack of reports submitted by victims, to weaknesses in the investigation, prosecution and trial processes. This research aims to conduct a juridical analysis of law enforcement in cases of rape of minors in Indonesia. By taking a juridical approach, this research will explore legal aspects related to handling cases of rape of minors, including criminal provisions, court procedures, and legal protection for child victims.